ASAI ISOLAT BAKTERI KITINOLITIK BACILLUS SP. BK17 PADA MEDIA PEMBAWA TANAH GAMBUT DAN KOMPOS JANJANG KELAPA SAWIT DALAM MENGHAMBAT PERTUMBUHAN JAMUR PATOGEN SCLEROTIUM ROLFSII DAN FUSARIUM OXYSPORUM PADA KECAMBAH CABAI - Hutauruk, Deswidya; Suryanto, Dwi; Munir, Erman (Universitas Lampung, 2016)
Assay of chitinolytic bacterial isolate of Bacillus sp. BK17 in peat and palm oil bunch compost as carrier media in inhibiting Sclerotium rolfsii and Fusarium oxysporum of chilli seedlings. Sclerotium rolfsii and Fusarium oxysporum have been known as causal agents of seedling-off of chilli. Biological control has been used as an alternative control to replace chemical control. This study was aimed to determine the viability and ability of chitinolityc bacteria Bacillus sp. BK17 in carrier media of peat and palm oil bunch compost and in growing media to control seedling-off caused by S. rolfsii dan F. oxysporum of chilli. Our previous study showed that Bacillus sp. BK17 could reduce disease severity and intensity. Bacterial viability was measured as colony number grown after 90 days of storage in minimum salt medium with colloidal chitin as sole C source. Reduction of disease infection was measured as seedling number infected by S. rolfsii dan F. oxysporum. Seedling performances were measured as seedling height, leaf number and dry-weight after 30-days of growth. The result showed that bacterial cell viability was still high in both peat and palm oil bunch compost both with and without colloidal chitin addition after 90 days of storage. It was also shown that during application bacterial cell could grow. Seedling performaces i.e. seedling height, leaf number and dry-weight showed to be normal or even increase compared to those of pathogenic fungal inoculation only and (-) control.